Examining the Relationship Between the Leadership Levels and Authenticity of the Students in the Department of Recreation - Reha Bozgüney, Serdar Büyükipekci (Pakistan Journal of Medical & Health Sciences, 2022)
This study aims aimed to examine the relationship between the leadership levels and authenticity of the students in the Department of Recreation in terms of certain variables. The population of the study consisted of students of department of recreation studying in sports sciences faculties and schools of physical education and sports. The variance and homogeneity of the obtained data were tested, and for the data determined to be homogeneous, Independent t-test was used in binary comparisons while One Way Anowa test was used in multiple comparisons, and Tukey HSD test was used to determine the source of difference. For the statistical analysis and interpretation of the data, p<0,05 significance level was taken into consideration. It was found that the mean values of athletes were statistically higher compared to sedentary people in all Leadership dimensions depending of sportiveness factor (p<0.05) while again the mean values of athletes were statistically higher compared to sedentary people in all dimensions except Impartiality within authenticity dimensions (p<0.05). Depending on the age factor, it was determined that the mean value of the 18-21 age group in the Group sub-dimension of the Leadership dimension was statistically higher compared to the 26 and older age group (p<0.05). In all of the authenticity dimensions, it was determined that the values decreased as the age group increased and this change was statistically significant (p<0.05). A positive correlation was found between the leadership and authenticity values, and it was determined that the authenticity increased at the same rate as the leadership characteristics increased. In the light of these findings, it can be said that women are more authentic and unbiased compared to men, the leadership and authenticity values of the athletes are more positive compared to sedentary people, the mean values of the authenticity dimension decrease statistically as the age group increases, and there is a positive relationship between the leadership and authenticity values of the students. It can be said that this situation observed between women and men may be due to the responsibilities and roles imposed on women and men in society, sportive life has a positive effect on the leadership and authenticity characteristics, and the increase in leadership and authenticity characteristics will affect each other positively.